Targeting mitochondria for ovarian aging: new insights into mechanisms and therapeutic potential - Wang, Zi-Han; Wang, Zhen-Jing; Liu, Huai-Chao; Wang, Chen-Yu; Wang, Yu-Qi; Yue, Yang; Zhao, Chen; Wang, Guoyun; Wan, Ji-Peng (Frontiers in Endocrinology, 2024)
Ovarian aging is a complex process characterized by a decline in oocyte quantity and quality, directly impacting fertility and overall well-being. Recent researches have identified mitochondria as pivotal players in the aging of ovaries, influencing various hallmarks and pathways governing this intricate process. In this review, we discuss the multifaceted role of mitochondria in determining ovarian fate, and outline the pivotal mechanisms through which mitochondria contribute to ovarian aging.Specifically, we emphasize the potential of targeting mitochondrial dysfunction through innovative therapeutic approaches, including antioxidants, metabolic improvement, biogenesis promotion, mitophagy enhancement, mitochondrial transfer, and traditional Chinese medicine. These strategies hold promise as effective means to mitigate age-related fertility decline and preserve ovarian health. Drawing insights from advanced researches in the field, this review provides a deeper understanding of the intricate interplay between mitochondrial function and ovarian aging, offering valuable perspectives for the development of novel therapeutic interventions aimed at preserving fertility and enhancing overall reproductive health.